2017
DOI: 10.1093/hmg/ddx201
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that phosphorylated ubiquitin signaling is involved in the etiology of Parkinson’s disease

Abstract: The ubiquitin (Ub) kinase PINK1 and the E3 Ub ligase Parkin, two gene products associated with young-onset Parkinson's disease (PD), participate in mitochondrial quality control. The phosphorylation of mitochondrial polyUb by PINK1, which is activated in a mitochondrial membrane potential (ΔΨm)-dependent manner, facilitates the mitochondrial translocation and concomitant enzymatic activation of Parkin, leading to the clearance of phospho-polyUb-tagged mitochondria via mitophagy. Thus, Ub phosphorylation is a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 53 publications
7
34
0
Order By: Relevance
“…Although we showed that PINK1 deficiency resulted in a significant reduction in the density of Ser65-pUb-positve cells, several Ser65-pUb-positive cells were detected in the hippocampus of PINK1 −/− mice. Notably, PINK1-independent Ser65-pUb signals were observed in regions adjacent to the PPM2 cluster in Drosophila lacking PINK1 [27]. These findings suggest that one or more uncharacterized kinases other than PINK1 produce Ser65-pUb.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Although we showed that PINK1 deficiency resulted in a significant reduction in the density of Ser65-pUb-positve cells, several Ser65-pUb-positive cells were detected in the hippocampus of PINK1 −/− mice. Notably, PINK1-independent Ser65-pUb signals were observed in regions adjacent to the PPM2 cluster in Drosophila lacking PINK1 [27]. These findings suggest that one or more uncharacterized kinases other than PINK1 produce Ser65-pUb.…”
Section: Discussionmentioning
confidence: 83%
“…Ubiquitin phosphorylation at Serine 65 is a key step in the efficient execution of PINK1/Parkin-dependent mitophagy [8]. The physiological and pathological importance of ubiquitin phosphorylation has been suggested [27][28][29]. However, immunohistochemical data on ubiquitin phosphorylation are scarce in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations